Review of legal and equitable property rights - LAU, Kwan Ho (Institutional Knowledge at Singapore Management University, 2020)
There can be few briefs in private law more challenging than that of answering the question: What is property? That inquiry may be undertaken on so many planes that it can seem at once monumental and Sisyphean. Many have been content to skirt the edges of the debate, perhaps by limiting their investigations within a narrow compass, or by assuming the correctness of a proposition that ought in fairness to require deeper examination. Not so for Professor John Tarrant, who in a significant contribution has tackled the problem squarely.